Evaluation of SfM against tradional stereophotogrammetry and LiDAR techniques for DSM creation in various land cover areas - Wenger, Sebastian Michael Benedict (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.